The signs of sin seriousness of offence in biblical law - Burnside, Jonathan P. (Jonathan Patrick) (Sheffield : Sheffield Academic Press, 2003)
What makes one crime more serious than another, and why? This book investigates the problem of "seriousness of offence" in English law from the comparative perspective of biblical law. Burnside takes a semiotic approach to show how biblical conceptions of seriousness are synthesised and communicated through various descriptive and performative registers. Seven case studies show that biblical law discriminates between the seriousness of different offences and between the relative seriousness of the same offence when committed by different people or when performed in different ways. Re
List of Figures; Foreword; Acknowledgments; Abbreviations; Introduction; Chapter 1 DETERMINING SERIOUSNESS OF OFFENCE IN BIBLICAL LAW; Chapter 2 THE WRATH OF GOD ON THE SONS OF DISOBEDIENCE: SERIOUSNESS OF OFFENCE AND DEUTERONOMY 21.18-21; Chapter 3 LINEAGE, TITLE AND THE BAREFOOT MAN: SERIOUSNESS OF OFFENCE AND DEUTERONOMY 25.5-10; Chapter 4 PROSTITUTION AND THE JEALOUSY OF GOD AND MAN: SERIOUSNESS OF OFFENCE IN LEVITICUS 21.9 AND DEUTERONOMY 22.20-21; Chapter 5 SIN, STATUS AND SACRIFICE: SERIOUSNESS OF OFFENCE AND LEVITICUS 4:1-35
Includes bibliographical references (p. [254]-267) and indexes.
Description based on print version record.
Keywords: Criminal law (Jewish law); Law (Theology) -- Biblical teaching; Bible. -- Criticism, interpretation, etc; Law (Theology); Bible; x; RELIGION -- Christian Theology -- Ethics; Oude Testament; Wet (gebod Gods); Overtredingen; Electronic books